The effect of specialized training and human technology capability on police performance in Abu Dhabi: Preliminary study - Hakimi, Halimaton Saadiah; Abboud Aiyammahi, Ali Khameis Ali; Robani, Anidah (Human Resource Management Academic Research Society, 2024)
Police performance, defined as the execution of actions, tasks, or functions, has been a critical concern in Abu Dhabi and worldwide. In Abu Dhabi, the suboptimal performance of police forces has hindered crime-fighting efforts and compromised community safety. This under performance is primarily attributed to inadequate specialized training and poor integration of human technology capabilities, which together undermine the efficiency and effectiveness of police officers. The COVID-19 pandemic exacerbated these challenges, making it difficult for officers to promote safety, maintain active duty, and protect lives and properties. This study investigates the potential of human-technology capability to bridge the gap between specialized training and police performance. It specifically examines the relationship between specialized training, human-technology capability, and officer performance at the Abu Dhabi Police Academy, with a focus on the mediating effect of human-technology capability on this relationship. A quantitative research approach was employed, utilizing a survey strategy designed to minimize bias and align with a positivist research model. Simple random sampling was used to collect primary data through face-to-face self-administered surveys and emailed questionnaires. Out of 355 questionnaires distributed, 336 valid responses were received, achieving a 94.7% response rate. The data were analyzed using SPSS and SmartPLS (PLS-SEM) with various statistical tools, including descriptive analysis, exploratory factor analysis, and reliability testing. The results indicate a significant relationship between specialized training, human-technology capability, and officer performance. The findings show that both specialized training and human-technology capability positively impact officer performance, with human-technology capability serving as a mediator in this relationship. These insights are crucial for enhancing police performance, particularly in protecting the community and improving crime detection during the COVID-19 pandemic through technological means. The study’s findings are expected to benefit the Abu Dhabi Police Academy by increasing public safety and contributing to the city’s economic growth.